滚轮轴线空间夹角检测方法探讨 - 王国民; 姚正秋; 李国平; 马礼胜; 王建涛 (Jixie Chuandong, 2005)
The ideal position of axes of roll and disk is parallel to each other in rolling drive.But,in fact,there is a skew angle between axes of roller and disk due to the mounting errors.The skew angle will infect the drive precision.For this reason,three detecting methods are proposed in this paper.They are optical-mechanical method,displacement detecting method and direct adjustment method.All these methods are applied in the experiment and the results are very well.With the help of first two methods,the skew angle between roller and disk axes is controlled under 30 arcseconds.After applying the first method,experiments show that the friction drive can achieve high precision in the ultra slow speed.The lowest long-steady velocity of the experiment drive system is 0.2″/s with corresponding precision 0.01 arcsend（RMS）,and during 30 minutes the lowest steady velocity is 0.05″/s with corresponding precision 0.009 arcsend（RMS）.All these methods given in this paper are useful for other drive system and precision mechani